Estudo exploratório sobre tentativas de suicídio por medicamento em uma instituição pública de saúde em Fortaleza - Julião, Antonio Osmar Ribeiro (1998)
The present work is an Pharmacoepidemiology approach of suicide attempts by drugs in Fortaleza. This in an epidemiology study, made from january, 01 to dezembre, 31 in 1997. It was elaboreted from 824 patienVs samples sellected from suicide attempt popuiation at instituto Dr. José Frota Hospital. The data were collected from the handbooks in the Toxicological Assistence Center of Ceará. It has been prooved that there. is a high levei on suicide attempts in Fortaleza with na average of 39,6 to 100.000 inhabitants. Womem has prevaled with 670 (81,3%) cases. The average age of the popuiation in the study was years old. The drugstores in the city were pointed as the spots of aquisition where people bonght the drugs, with 508 (91,4%) cases. Students were in the rank of the most mentioned, with 124 cases. The most used drug was diazepam, 233 (27,1%) cases, and the most frequent symptpn among them was been sleepy with 281 (34,1) cases.